Manifestasi Rasa Syukur Dan Analisis Dedikasi Dr. Amaliyah, S.Ag., M.A., MOS., MCE., MCF - Vina Inayatul Matin; Saepur Rijal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study aims to deeply analyze the intellectual dedication and manifestation of Dr. Amaliyah's vision in transforming student managerial competencies and character through the educational process. The background of this research is based on the phenomenon of rigid academic curriculum that often separates theory from practical reality, where Dr. Amaliyah's figure is present to break this stigma through an innovative teaching style and humanistic methodology. Using the intellectual study method (intellectual study) with a qualitative narrative approach, data were collected through participatory observation and documentation of the subject's learning experiences for five semesters. The main results show that the application of the theory of Experiential Learning and Teacher-Student Relationship by the figure proved effective in transforming students' conceptual understanding into practical skills, especially in mastering the National Education Standards and POACE-based training management. The most important result is the discovery of synchronization between micro-leadership with integrity and digital innovation, which culminated in national recognition of the “Curriculum of Love” and the development of the Central of World Knowledge (CWK). These findings conclude that the figure's dedication is not merely a transfer of knowledge, but a scaffolding process that integrates intellectual intelligence with spiritual depth. The implication is that this study recommends Dr. Amaliyah's leadership model as an ideal prototype for educators in the Education 4.0 era who want to align the institution's strategic vision with compassion-based human empowerment.